Effect of private insurance incentive policy reforms on trends in coronary revascularisation procedures in the private and public health sectors in Western Australia: A cohort study - Trafalski, S.; Briffa, T.; Hung, J.; Moorin, Rachel; Sanfilippo, F.; Preen, D.; Einarsdottir, K. (BioMed Central, 2013)
Background: The Australian federal government introduced private health insurance incentive policy reforms in 2000 that increased the uptake of private health insurance in Australia. There is currently a lack of evidence on the effect of the policy reforms on access to cardiovascular interventions in public and private hospitals in Australia. The aim was to investigate whether the increased private health insurance uptake influenced trends in emergency and elective coronary artery revascularisation procedures (CARPs) for private and public patients. Methods: We included 34,423 incident CARPs from Western Australia during 1995-2008 in this study. Rates of emergency and elective CARPs were stratified for publicly and privately funded patients. The average annual percent change (AAPC) in trend was calculated before and after 2000 using joinpoint regression. Results: The rate of emergency CARPs, which were predominantly percutaneous coronary interventions (PCIs) with stenting, increased throughout the study period for both public and private patients (AAPC=12.9%, 95% CI=5.0,22.0 and 14.1%, 95% CI=9.8,18.6, respectively) with no significant difference in trends before and after policy implementation. The rate of elective PCIs with stenting from 2000 onwards remained relatively stable for public patients (AAPC=−6.0, 95% C= −16.9,6.4), but increased by 4.1% on average annually (95% CI=1.8,6.3) for private patients (Pdifference=0.04 between groups). This rate increase for private patients was only seen in people aged over 65 years and people residing in high socioeconomic areas.Conclusions: The private health insurance incentive policy reforms are a likely contributing factor in the shift in 2000 from public to privately-funded elective PCIs with stenting. These reforms as well as the increasing number of private hospitals may have been successful in increasing the availability of publicly-funded beds since 2000.